Optimal algorithm based on weight balancing for designing the logical topology of the optical network - FU Ming-lei; LE Zi-chun; LU Min (Tongxin xuebao)
The design of an optimal logical topology in optical networks was reported.The traffic load matrix and the delay matrix were considered together and then two novel network weights were defined.Therefore,both the congestion and average delay were optimized simultaneously.Moreover,an optimal algorithm which based on the two kinds of weight definition was proposed.In the simulation part,the NSFNET was chosen as the network model and the heuristic algorithm was compared with two other kinds of designing algorithms.Finally,the effect on network performances,which was caused by four performance parameters including the congestion,blocking probability,delay and load balanc-ing states,was discussed in numerical results part.